Three species of Phymatodes Mulsant (Coleoptera: Cerambycidae) new to South Korea that hosted on Vitis vinifera Linnaeus (Vitaceae). Issue 1 (7th January 2013) - Lim, Jongok; Kim, Il‐Kwon; Lee, Young‐Su; Kim, Kyung‐Mi; Kim, Chul‐Hak; Lim, Jong‐Su; Park, Shin‐Young; Lee, Bong‐Woo
Abstract Two unrecorded Phymatodes species, P. (Phymatodellus) jiangi Wang and Zheng, P. (P.) zemlinae Plavilstshikov and Anufrieva, and a known species from North Korea, P. (P.) murzini Danilevsky, are newly recognized in South Korea, as insect pests of Vitis vinifera Linnaeus (Vitaceae). In the present paper, male genitalia of P. (P.) jiangi Wang and Zheng is presented for the first time. We also provide the diagnoses and illustrations of habitus of three Phymatodes species with a revised key to Korean species.